Profit Analysis and B/C Ratio Hydroponic Vegetable Farming At PT. Central Bengkulu City - Lelyta Sirait; Ana Nurmalia; Yossie Yumiati (Baselang, 2021)
Hydroponics is a technology for growing without soil, using nutrient solutions in water. Vegetables hydroponically is more hygienic without pesticides and fresh. The selling price of vegetables hdroponik also higher than conventional vegetable. However, the high cost on the level of investment and operating costs to be one important factor to be researched is it still efficient to run. The purpose of this study is to analyze the income of the hydroponic farming of vegetables and analyze the needs of the vegetables usahtani in the P.T Central. The method of determining the area used in this research is Purposive, while the method of analysis of the likelihood ratio of the profit and efeiciency level, B/C ratio. The results showed the average profit of farm in the PT. Central is Rp. 29.674.000,- per season and Farming system vegetables hydroponics worth to cultivated of PT. Central.